Allocating Family Responsibilities for Dependent Older People in Mexico and Peru. Issue 4 (3rd April 2018) - Lloyd-Sherlock, Peter; Mayston, Rosie; Acosta, Alberto; Gallardo, Sara; Guerra, Mariella; Sosa, Ana Luisa; Montes de Oca, Veronica; Prince, Martin
Abstract: This paper applies different analytical frameworks to explore processes of family bargaining about providing care for dependent older people in Mexico and Peru. These frameworks include cultural norms, life course effects and material exchange. The paper is based on 19 in-depth qualitative family case studies, which are linked to a wider set of quantitative survey data. Care arrangements and bargaining processes are revealed to be highly gendered, and largely conform to prevailing cultural norms. Rather than neutral and objective, the self-identified role as main carer is found to be subjective and potentially ambiguous. The few men who self-identify as main carers are more likely to play an indirect, organisational role than engage directly in daily care. As such, bargaining mainly relates to which woman performs the main care role, and large family networks mean that there is usually more than one candidate carer. Bargaining can occur inter-generationally and conjugally, but bargaining between siblings is of particular importance. Bargaining is framed by the uncertain trajectory of older people's care needs, and arrangements are sometimes reconfigured in response to changing care needs or family circumstances. Taking the narratives at face value, the influence of life course effects on bargaining and care arrangements is more obvious than material exchange. There are, however, indications that economic considerations, particularly inheritance, still play an important behind the scenes role.